The Labour Market Effects of Alma Mater : Evidence from Italy - Giorgio Brunello; Lorenzo Cappellari (Institute for the Study of Labor (IZA), 2005)
We use data from a nationally representative survey of Italian graduates to study whether Alma Mater matters for employment and earnings three years after graduation. We find that the attended college does matter, and that college related differences are substantial both among and within regions of the country. However, these differences are not large enough to trigger substantial mobility flows from poorly performing to better performing institutions. There is also evidence that going to a private university pays off at least in the early part of a career: the employment weighted college wage gains from going to a private college are close to 18 percent. Only part of this gain can be explained by the fact that private universities have lower pupil - teacher ratios than public institutions.
Keywords: J24; 330; college education; Italy